2018
DOI: 10.4274/jcp.2018.0022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quality of Life of Patients Followed up with Diagnosis of Type 1 Diabetes Mellitus

Abstract: GİRİŞ ve AMAÇ: Kronik hastalıklarda yaşam kalitesi düzeyi çok önemlidir. Tip 1 diyabetes mellitus tanılı çocuk ve ergenlerde yaşam kalitesi düzeyinin saptanması, aynı yaş grubundaki sağlıklı çocuklara göre kıyaslama yapılması ve bu sonuçların, çocukların ve ailelerinin sosyodemografik özellikleri ile ilişkisinin değerlendirilmesi amaçlandı. YÖNTEM ve GEREÇLER:Çalışmaya tip 1 diyabetes mellitus tanısı ile takip edilen 4-16 yaş arası 45 çocuk ve genel pediatri polikliniğine başvuran benzer demografik özelliklere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, it is reported that it will reach 417.3 million in 2030 and 486.1 million in 2045, and it will increase even more in both men and women (4). Diabetes, which causes changes in the lifestyle of individuals due to the need for continuous follow-up and treatment, negatively affects the quality of life of the individual, which is a comprehensive structure that includes physical, emotional, and social aspects (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is reported that it will reach 417.3 million in 2030 and 486.1 million in 2045, and it will increase even more in both men and women (4). Diabetes, which causes changes in the lifestyle of individuals due to the need for continuous follow-up and treatment, negatively affects the quality of life of the individual, which is a comprehensive structure that includes physical, emotional, and social aspects (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In the studies in the literature, it has been reported that gender affects the quality of life of individuals as well as factors such as diabetesrelated complications, age, drug intake routes, profession, and physical activity level (5)(6)(7). It is emphasized that the differences observed between women and men are related to various underlying causes, and the effects such as bone loss and gastrointestinal side effects that develop in the treatment selection or treatment process related to gender are more a matter of concern for women (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%